Atretic Parietal Cephalocele with Persistent Falcine Sinus and Sinus Pericranii: A Rare Case Diagnosed on Prenatal Ultrasound - Pancholi, Alpesh D.; Makam, Adinarayana (Journal of Fetal Medicine, 2025)
Atretic parietal cephaloceles (APCs) are the herniation of intracranial structures like vestigial tissues (i.e., glial tissue, arachnoid tissue, or neural rests) and meninges through a cranial vault defect. These are small skin covered scalp lesions that usually occur near the lambda. The most common site is the parietal region, followed by the occipital region. Atretic cephaloceles are usually associated with intracranial venous abnormalities such as persistent falcine sinus (PFS). Association of APC and sinus pericranii (SP) is very rare. APC can be isolated or associated with intracranial abnormalities, with callosal dysgenesis, holoprosencephaly spectrum, or interhemispheric cyst being the most common. We report a case of APC with absence of straight sinus, PFS, and SP diagnosed at mid trimester on prenatal ultrasound in a diabetic mother. The diagnosis of APC was confirmed on clinical examination postnatally.
Keywords: atretic cephalocele; atretic parietal cephalocele; persistent falcine sinus; scalp lesion; sinus pericranii